(untitled) - Vitale, Joe (Hoboken, N.J., 2006)
In "Meet and Grow Rich" the authors share the practical and necessary "what to do" and the "how to do it" info that can help anyone to easily create a successful mastermind group of their own. I especially liked Chapter 9 which provides real world, inspiring examples of how others have used mastermind groups to achieve both personal and professional success beyond their wildest dreams. The Q & A format of Chapter 10 answers the most common questions about masterminding and mastermind groups. Part II of the book gives other experts an opportunity to share their valuable knowledge, experience and insights into masterminding. Having participated in mastermind groups myself, I also appreciated the books helpful info on how to invite and select members, how to structure your mastermind sessions for maximum effectiveness, how to deal with different personalities in the group and how to easily resolve any challenges that may arise.
Keywords: Success in business,Success,Business networks; Social aspects,Social aspects